1972
DOI: 10.1104/pp.49.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins in Seedling Roots of Pea

Abstract: The natural occurrence of cytokinins existing both in a free form and as a constituent of transfer RNA was examined in serial segments of young seedling roots of pea. Purified ethanol extracts of root apices were resolved into four factors capable of inducing soybean callus tissue proliferation. The most active factor was identified as zeatin or some closely related compound; it produced polyploid divisions and tracheary element differentiation when tested on cultured pea root segments. 2Abbreviations: IPA: 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
2

Year Published

1972
1972
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(87 citation statements)
references
References 36 publications
(32 reference statements)
6
79
0
2
Order By: Relevance
“…The increase in ,ug KE/g dry weight of bacteria between day 2 and day 3 was reproducible in different experiments and probably reflected an increase in metabolic rates during the rapid growth phase. The decrease in detectable cytokinin between day 3 and day 10 indicates that these compounds were either inactivated, metabolized, or masked by inhibitors. No cytokinin activity was detected in a 1.1 liter sample of day 0 cultures.…”
mentioning
confidence: 99%
“…The increase in ,ug KE/g dry weight of bacteria between day 2 and day 3 was reproducible in different experiments and probably reflected an increase in metabolic rates during the rapid growth phase. The decrease in detectable cytokinin between day 3 and day 10 indicates that these compounds were either inactivated, metabolized, or masked by inhibitors. No cytokinin activity was detected in a 1.1 liter sample of day 0 cultures.…”
mentioning
confidence: 99%
“…Studies by Erance (1980) with Pinus proposed that nitrogen is an effector of cytokinin ponderosa Laws, inoculated with P. tinctorius also production and thus regulates the metabolic activity revealed that total biomass, lateral root numbers, of plants in response to their mineral nutrition, and short-root numbers were significantly greater in Although these studies emphasized shoot nutrition inoculated than in non-inoculated seedlings. In as an important regulator of phytohormone biocontrast, Coleman, Bledsoe & Smit (1990) observed synthesis, the mineral status of roots may be equally that inoculation of Pseudotsuga menziesii with important since root apices are an active source of Hebeloma crustuliniforme and Rhizopogon vinicolor cytokinins (Short & Torrey, 1972). decreased root dry weight, total plant biomass, and…”
Section: Discussionmentioning
confidence: 99%
“…Roots are considered the major the ectomycorrhizal association, site of cytokinin synthesis (Short & Torrey, 1972; Recent improvements in the separation and deEeldman, 1975), and therefore, stimulated lateral tection of cytokinins using high-pressure liquid short-root production, as seen with 12-month-old chromatography coupled with mass spectrometry, seedlings, and enhanced total root dry weight of 14-and cytokinin-specific immunoassays offer a tremenmonth-old seedlings, may have provided additional dous tool to plant scientists. Application of these sources of cytokinin supply in the host plant, technologies to investigate hormonal relationships in Wheeler, Henson & McLaughlin (1979) suggested symbiotic associations could rapidly expand our that increased foliar cytokinins in Alnus glutinosa knowledge of microbe-host interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional upstream sequence information was obtained by gene-specific PCR extension from the library clone (described in Bassett et al 2000) and included approximately 1144 bp upstream of the putative translation initiation site. Total RNA was isolated according to the procedure of Short and Torrey (1972) from cotyledons, first leaves and roots obtained from plants sampled 5 and 6 days after short-day induction of flowering (induced) or continuous exposure to light (vegetative). cDNA was prepared from total morning glory RNAs using the Advantage RT for PCR kit (Clontech, Palo Alto, Calif.) and a combination of random hexamers and oligo(dT) to prime cDNA synthesis (Bassett et al 2000).…”
Section: Tools Used For In Silico Promoter Analysismentioning
confidence: 99%